2006
DOI: 10.1080/14786430600606834
|View full text |Cite
|
Sign up to set email alerts
|

About the importance of introducing a correction factor in the Sneddon relationship for nanoindentation measurements

Abstract: To cite this version:Michel Troyon, Sébastien Lafaye. About the importance of introducing a correction factor in the Sneddon relationship for nanoindentation measurements. Philosophical Magazine, Taylor & Francis, 2006, 86 (33-35) AbstractIn the Sneddon relationship between unloading contact stiffness, elastic modulus and contact area, it is absolutely necessary to introduce a correction factor α to perform good elastic modulus and hardness measurements by nanoindentation. This is verified in the present pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…␤ is a numerical factor, which is usually assumed to be 2/ 1/2 ‫ס‬ 1.128. Recent authors [22][23][24] have reported that the conventional value is too low and that the actual value, which varies a little depending on specimen properties and indenter shape, is closer to 1.2. At present, we find that ␤ ≅ 1.23 works best based on our analysis of indents placed in a fused silica standard.…”
Section: A Standard Oliver-pharr Analysismentioning
confidence: 93%
“…␤ is a numerical factor, which is usually assumed to be 2/ 1/2 ‫ס‬ 1.128. Recent authors [22][23][24] have reported that the conventional value is too low and that the actual value, which varies a little depending on specimen properties and indenter shape, is closer to 1.2. At present, we find that ␤ ≅ 1.23 works best based on our analysis of indents placed in a fused silica standard.…”
Section: A Standard Oliver-pharr Analysismentioning
confidence: 93%
“…(7) should have a correction factor different from 1 and dependent on both indenter geometry and Poisson's coefficient. 22,23 Other works [8][9][10][11][12] found dependence of b in relation to the indentation size and, consequently, in relation to the indenter tip defects. …”
Section: Indentation Variablesmentioning
confidence: 99%
“…[4][5][6] In these cases, the changes in the shape of the loading curve can also be confused with those caused by the material work hardening, 7 which leads to errors in the calculation of the work-hardening coefficient. Furthermore, significant changes on the correction factor b, used to adjust Sneddon's equations, [8][9][10][11][12] have been recently observed due to indenter tip roundness.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has been suggested that the effect of the indentation size is caused by tip roundness effects 5,32,33 ; yet the effect caused by the ratio R/h max reported in Refs. 5, 32, and 33 was obtained by an increment of h max while maintaining a constant radius.…”
Section: F Correction Factor Of the Sneddon's Equationmentioning
confidence: 99%
“…(4), 23 where b is a correction factor, which is dependent on both indenter geometry and Poisson's coefficient. [27][28][29] Other works have shown dependence of b with the indentation size when the indenter tip presents some roundness 5,[30][31][32][33] and with the indenter elastic deformation.…”
Section: Indentation Variablesmentioning
confidence: 99%